Počítat je hračka - koukej na Ušáčka! - Mac Cue, Dick; McCue, Lisa; Mac Cue, Dick; McCue, Lisa; Štíplová, Ljuba, 1930- (Bratislava : Egmont ČSFR, 1991)
Se zajíčkem se pomocí obrázků a veršů v leporelu děti učí číst a počítat